Developing an online, searchable database to systematically map and organise current literature on retention research (ORRCA2). (February 2022) - Kearney, Anna; Ashford, Polly-Anna; Butlin, Laura; Conway, Thomas; Cragg, William J; Devane, Declan; Gardner, Heidi; Gaunt, Daisy M; Gillies, Katie; Harman, Nicola L; Hunter, Andrew; Lane, Athene J; et al.
Background: Addressing recruitment and retention challenges in trials is a key priority for methods research, but navigating the literature is difficult and time-consuming. In 2016, ORRCA (www.orrca.org.uk ) launched a free, searchable database of recruitment research that has been widely accessed and used to support the update of systematic reviews and the selection of recruitment strategies for clinical trials. ORRCA2 aims to create a similar database to map the growing volume and importance of retention research. Methods: Searches of Medline (Ovid), CINAHL, PsycINFO, Scopus, Web of Science Core Collection and the Cochrane Library, restricted to English language and publications up to the end of 2017. Hand searches of key systematic reviews were undertaken and randomised evaluations of recruitment interventions within the ORRCA database on 1 October 2020 were also reviewed for any secondary retention outcomes. Records were screened by title and abstract before obtaining the full text of potentially relevant articles. Studies reporting or evaluating strategies, methods and study designs to improve retention within healthcare research were eligible. Case reports describing retention challenges or successes and studies evaluating participant reported reasons for withdrawal or losses were also included. Studies assessing adherence to treatments, attendance at appointments outside of research and statistical analysis methods for missing data were excluded. Eligible articles were categorised into one of the following evidence types: randomised evaluations, non-randomised evaluations, application of retention strategies without evaluation and observations of factors affecting retention. Articles were also mapped against a retention domain framework. Additional data were extracted on research outcomes, methods and host study context. Results: Of the 72, 904 abstracts screened, 4, 364 full texts were obtained, and 1, 167 articles were eligible. Of these, 165 (14%) were randomised evaluations, 99 (8%) non-randomised evaluations, 319 (27%) strategies without evaluation and 584 (50%) observations of factors affecting retention. Eighty-four percent (n = 979) of studies assessed the numbers of participants retained, 27% (n = 317) assessed demographic differences between retained and lost participants, while only 4% (n = 44) assessed the cost of retention strategies. The most frequently reported domains within the 165 studies categorised as 'randomised evaluations of retention strategies' were participant monetary incentives (32%), participant reminders and prompts (30%), questionnaire design (30%) and data collection location and method (26%). Conclusion: ORRCA2 builds on the success of ORRCA extending the database to organise the growing volume of retention research. Less than 15% of articles were randomised evaluations of retention strategies. Mapping of the literature highlights several areas for future research such as the role of research sites, clinical staff and study design in enhancing retention. Future studies should also include cost–benefit analysis of retention strategies.